Percutaneous absorption of solvent vapors in man. - Riihimäki, Vesa; Pfäffli, Pirkko (Scandinavian Journal of Work, Environment & Health, 1978)
It is known from industrial experience and experimental studies that percutaneous absorption of concentrated liquid solvents may be considerable and even hazardous if large enough areas of skin are exposed for long periods of time. Percutaneous penetration of xylene, styrene, toluene, 1,1,1-trichloroethane and tetrachloroethylene vapors at ambient air concentrations of 600 ppm for 3.5 h was studied in a dynamic exposure chamber with a restricted number of human volunteers. Although the small number of exposed persons precluded conclusive quantitation of absorption and valid intercompound comparisons, aromatic solvents and tetrachloroethylene appear to penetrate skin much more readily than 1,1,1-trichloroethane. Skin penetrating properties of solvents seem, under the circumstances, to be associated primarily with lipid solubility. It was approximated that percutaneous exposure (total body surface) to 600 ppm of xylene vapor for 3.5 h corresponded to an equally long inhalation exposure of less than 10 ppm. Similar percutaneous exposure to 1,1,1,-trichloroethane corresponded to an inhalation exposure of only 0.6 ppm. Disease-affected skin may display altered permeability characteristics, and one volunteer with atopic dermatitis exhibited a more than three times larger absorption of xylene vapor when compared to subjects with normal skin. It may be concluded that in the work environment percutaneous absorption of solvent vapors from the surrounding air through undamaged skin is likely to be insignificant.
Keywords: 1,1,1-trichloroethane; human exposure; m-xylene; man; percutaneous absorption; solvent; solvent vapor; styrene; tetrachloroethylene; toluene; vapor